FERTILIZER IN INCREASING SOIL FERTILITY - Uralova Ferangiz; Khujayeva Komila; Shukurov Timur Esanmurod o‘g‘li; Esonov Ulug‘bek Nurilla o‘g‘li; Khushanov Khurshid Muhiddin o‘g‘li; Kulmanov B. P. (Journals Park Publishing, 2025)
This article presents the reduction of nitrite and nitrate content in the soil and food crops by safe and non-toxic fertilizing of agricultural crops through various methods of storage and neutralization of manure released by farm animals.
Keywords: Soil nitrite and nitrate fertilizer, hot method, macro-micro elements.